Endothelial Protein C Receptor - Esmon, Charles T.; Xu, Jun; Gu, Jian-ming; Qu, Dongfeng; Laszik, Zolton; Ferrell, Gary; Stearns-Kurosawa, Deborah J.; Kurosawa, Shichiro; Taylor, Fletcher B., Jr.; Esmon, Naomi L. (Thrombosis and Haemostasis, 1999)
The protein C anticoagulant pathway plays a critical role in the negative regulation of the blood clotting response. The pathway is triggered by thrombin, which allows the system to serve as an “on-demand” mechanism for limiting the coagulation response to injury. Specifically, the magnitude of the anticoagulant response is proportional to the level of thrombin generated.1 The clinical importance of the pathway is illustrated by the severe thrombotic complications associated with deficiencies of members of the pathway.2-4The protein C pathway is initiated when thrombin binds to thrombomodulin (TM)5 (Fig. 1). The surface of the endothelium constitutes the main site for protein C activation. The thrombin-TM complex is a potent activator of protein C, but it has little or no ability to activate platelets or clot fibrinogen. Therefore, TM serves as a molecular switch for thrombin, including thrombin’s macromolecular specificity and physiological function. Protein C activation is enhanced when protein C binds to the endothelial cell protein C receptor (EPCR).6 Endothelial cell protein C receptor augments protein C activation by increasing the affinity of the thrombin-TM complex for protein C.6-8 Not all protein C activation complexes involve EPCR since the levels of this protein are low in the microcirculation.9The thrombin-TM complex is rapidly inactivated by the protein C inhibitor10 and antithrombin11 (Fig. 1, bottom). Once activated protein C (APC) is formed, it proteolytically inactivates two critical blood clotting cofactors, factors Va and VIIIa,12,13 thereby limiting further thrombin formation. Activated protein C inactivates factor Va by cleaving at Arg506, which results in rapid but incomplete loss of activity, and Arg306.12 Cleavage at Arg306 results in complete inactivation of factor Va.Protein S serves as a cofactor for this process by increasing the affinity of APC for the membrane surface14-16 and by changing the specificity of the proteolytic cleavage of factor Va, which enhances cleavage at Arg306 without significantly modulating cleavage at Arg506.17 In addition, protein S blocks the ability of factor Xa to protect factor Va from inactivation by APC and has a similar function in the inactivation of the factor IXa-factor VIIIa complex.17 Furthermore, in combination with factor V, protein S enhances the ability of APC to inactivate factor VIII18,19 (Fig. 1, middle). Recently, there have been advances in understanding how protein S accomplishes these functions.Specifically, when protein S binds to APC, the distance from the active site of APC to the membrane surface is decreased about 1 nm.20 This decrease in distance is probably responsible for the ability of protein S to selectively increase the cleavage rate at Arg306. This conclusion is based on the observation that a protein C chimera has been prepared that, in the absence of protein S, has a distance between the membrane surface and its active site similar to that of the protein S-APC complex.21 With the chimera, protein S influences neither the distance to membrane surface nor the rate of cleavage of Arg306 in factor Va. Furthermore, the rate of cleavage at Arg306 for the chimera and the protein S-APC complex are almost identical.21Unlike most serine proteases, APC is resistant to inhibition by plasma proteinase inhibitors and circulates with a half-life of approximately 15 minutes.22 The half-life is determined by inhibition with the following plasma protease inhibitors: α1-antitrypsin,23 protein C inhibitor,24 and α2-macroglobulin25 (Fig. 1, bottom). Each contributes to APC inhibition.The clinical importance of this pathway is evident by the life-threatening thrombotic complications observed in infants with complete deficiencies of protein S or protein C.2 In the case of total protein C deficiency, these thrombotic complications are most commonly manifested as microvascular thrombosis of the skin (purpura fulminans). These lesions can be prevented by infusion of protein C, but they reappear if the protein C levels in the patient are allowed to decrease to low levels. Heterozygous deficiencies of protein C and protein S are more common with the frequency of protein C deficiency, occurring in 1 in 300 individuals.3,4 Heterozygous deficiencies of protein C or protein S alone are modest risk factors for thrombosis. In combination with other risk factors, however, these deficiencies substantially increase thrombotic risk.3,4The most common known risk factor for venous thrombosis, APC resistance, is also linked to the protein C pathway. Activated protein C normally inactivates factor Va by first cleaving at Arg506, followed by cleaving at Arg306.12,17,26 The most common basis for APC resistance is a dimorphism in factor V, which results in replacement of Arg506 with Gln. This substitution renders this bond resistant to cleavage by APC.27 This form of factor V is also termed factor V Leiden, because the molecular basis of the defect was identified in that city.28 As a result of the mutation, factor V Leiden inactivation requires cleavage at Arg306, which is a relatively slow process. Fortunately, as mentioned previously, protein S stimulates cleavage at Arg306.17 This observation may account for one of the reasons that protein S deficiency in combination with factor V Leiden results in a substantial increase in risk of thrombosis. Deficiencies in the protein C activation complex, most specifically TM, could also contribute to thrombotic risk. Recently, Öhlin et al identified mutations and polymorphisms in TM that appear to be associated with increased risk of myocardial infarction or venous thrombosis.29,30 Ireland et al31 identified alterations in the 5’ regulatory region of the TM gene in 5 of 104 patients with myocardial infarction. These mutations presumably reduce TM expression and contribute to the risk of myocardial infarction.31 Only 1 of 104 control, age matched individuals had any of these mutations. Mutations of TM also can lead to thrombosis in mice.32 Taken together, these observations provide a firm clinical basis to conclude that the members of this pathway are critical to adequate negative regulation of the blood clotting system.